PENGARUH KINERJA PERUSAHAAN, KEPEMILIKAN INSTITUSIONAL, DAN RISIKO TERHADAP KOMPENSASI EKSEKUTIF (Studi Empiris pada Industri Perbankan yang Terdaftar di BEI Periode 2017-2019) - Rafzan Fiqih Mahendra; Daljono Daljono (Diponegoro Journal of Accounting, 2022)
This study aimed to examine the effect of firm performance, institutional ownership, and risk on executive compensation where the variables used in this study are firm performance, institutional ownership, risk as independent variable and executive compensation as dependent variable.The population in this study are banking industries listed on the Indonesian Stock Exchange (IDX) in 2017-2019. Sample of this study selected by using purposive sampling method. There are 34 banking industries each year which fulfilled criterion as the research sample. The analytical method used in this research is multiple linear regression analysis.The result of this study indicate that firm performance and risk significantly affect executive compensation of banking industries in Indonesia. Meanwhile, institutional ownership didn’t significantly affect executive compensation of banking industries in Indonesia.